2015
DOI: 10.1002/pen.24127
|View full text |Cite
|
Sign up to set email alerts
|

Poly (3-hydroxybutyrate)/cellulose nanocrystal films for food packaging applications: Barrier and migration studies

Abstract: This article reports the fabrication of poly (3‐hydroxybutyrate) (PHB)/cellulose nanocrystal (CNC) based nanobiocomposite films with improved gas barrier and migration properties for food packaging applications. Acid hydrolysis of cellulose pulp from bamboo (Bambusabalcooa) yields CNCs with diameter of 15–20 nm and length of 400–600 nm. Evaluation of d‐spacing using XRD indicates intercalation of PHB matrix with CNC at optimum loadings of 2 wt%. Overall migration values in presence of both polar and nonpolar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 35 publications
5
62
0
Order By: Relevance
“…XRD diffractograms show that CSN peaks are absent at 2θ = 16.8° and are possibly overlapped by broader peaks from PLA, the intensity gets lower as the CSN loading is increased, which can also be seen as decrease in percentage crystallinity from ∼45% (1 wt %) to ∼39% (5 wt %). The peak at 2θ = 16.5° is most noticeable indication of the presence of CSN in the PLA/CSN bionanocomposites whose intensity drops with increment in loading . The plausible reason for decrease in crystallinity for 2 and 5 wt % could be agglomeration of CSN nanoparticles in the PLA matrix.…”
Section: Resultsmentioning
confidence: 98%
“…XRD diffractograms show that CSN peaks are absent at 2θ = 16.8° and are possibly overlapped by broader peaks from PLA, the intensity gets lower as the CSN loading is increased, which can also be seen as decrease in percentage crystallinity from ∼45% (1 wt %) to ∼39% (5 wt %). The peak at 2θ = 16.5° is most noticeable indication of the presence of CSN in the PLA/CSN bionanocomposites whose intensity drops with increment in loading . The plausible reason for decrease in crystallinity for 2 and 5 wt % could be agglomeration of CSN nanoparticles in the PLA matrix.…”
Section: Resultsmentioning
confidence: 98%
“…Fillers in this context refer to a variety of nanosized structures whose function is not only to fill the matrix but also to provide enhancement in properties such as barrier, optical, thermal, and mechanical . Particularly, PHB/cellulose nanocrystal (CNC) composites could also reduce additive migration to the food material in food packaging applications at low loadings, indicating that this material presents operational stability and can be used for products with long‐term storage at room temperature . Nanoscaled cellulose fibers are promising candidates for the preparation of bionanocomposites, owing to their high abundance, strength, stiffness, low weight, and biodegradability …”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the nanoparticles increased the tensile strength, Young's modulus and storage modulus of PHBV, and also acted as nucleating agent. Additionally, to the best of our knowledge, there have been few works concerning PHB and nanocellulose composites . Dhar et al focused their study on the thermal degradation kinetics as well as on the migration and barrier properties of PHB/cellulose nanocrystal (CNC) nanobiocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, to the best of our knowledge, there have been few works concerning PHB and nanocellulose composites . Dhar et al focused their study on the thermal degradation kinetics as well as on the migration and barrier properties of PHB/cellulose nanocrystal (CNC) nanobiocomposites. They concluded that PHB thermal stability was improved up to 3 wt% of CNC loading but with no significant change in activation energies nor in degradation mechanism.…”
Section: Introductionmentioning
confidence: 99%